Prescribing patterns and economic costs of proton pump inhibitors in Colombia (Colombia Medica, 2013)
Objective: To determine the prescribing patterns for proton pump inhibitors and to estimate the economic cost of their use in a group of patients affiliated with the Colombian Health System.Methods: This is a descriptive observational study. Data for analysis consisted of prescriptions dispensed between October 1st, 2010 and October 31st, 2010 and were collected from a systematic database of 4.2 million members. Socio-demographic variables were considered along with the defined daily dose, co-medication, convenience of the indication for proton pump inhibitor use and costs.Results: In this study, 113,560 prescriptions were dispensed in 89 cities, mostly to women (57.6%) with a mean age of 54.4 ± 18.7 yrs; the drugs were omeprazole (n= 111,294; 97.8%),  esomeprazole (n= 1,378; 1.2%), lansoprazole (n= 524; 0.4%), pantoprazole and rabeprazole. The indication for 87,349 of the formulas (76.9%) was justified and statistically associated with the use of NSAIDs, antithrombotics, corticosteroids, anti-ulcer, antibiotics and prokinetics. No justification was found for 26,211 (23.1%) of the prescriptions, which were associated with antidiabetics, antihypertensives, hypolipidemics and others (p